Kinerja Pelayanan Check In Counter di Bandar Udara Juanda Surabaya Berdasarkan Level of Services - Wahyoe Wahyoe (WARTA ARDHIA, 2011)
The Passenger of service equipment facility is a facility of quality and quantity that directly telt by the passengers. The Limitations of passenger service equipment facility will impact to build up the queue of passengers waiting to be serve. For example, check-in counter service facility is a passenger service facilities at terminal departure which often cause the queue. Leisure passengers at an airport is one of airport success in serving passengers. Related to the above, need to do an assessment of service performance check-in counter at Juanda airport in Surabaya based on the level of services.